Deriving configurable fragments for process design. (1st January 2014) - Assy, Nour; Chan, Nguyen Ngoc; Gaaloul, Walid; Defude, Bruno
In today's fast changing business environment, the business process design becomes a complex, time-consuming and error-prone task. Thus, many approaches have been proposed to facilitate the business process design phase. Some solutions such as defining and using process reference models or searching similar processes to a working one can facilitate the designer's work. However, recommending the whole process model can make the designer confused, especially in case of large-size business processes. In this paper, we propose an approach that assists the design phase with configurable process fragments. Concretely, we present an algorithm for merging process fragments around a particular activity to construct a consolidated fragment. This consolidated fragment is presented as a configurable sub-process that can be configured by the business process designer to create business process variants. The approach has been implemented as an extension of the Signavio Process Editor platform which is a web-based modelling tool for business processes. It has been also tested against a large collection of business process models taken from different domains. Experimental results show that our approach produces concise and efficient configurable fragments.